Significance of APTT as early predictor of bleeding in comparison to thrombocytopenia in dengue virus infection - B. T., Hamsa; S. V., Srinivasa; K., Prabhakar; A., Raveesha; A. G., Manoj (International Journal of Research in Medical Sciences, 2018)
Background: Dengue is a systemic viral infection transmitted by mosquitoes such as Aedes aegypti or Aedes albopictus. Dengue Fever (DF) is characterized by fever, headache, muscle or joint pain, and rash. The spectrum of dengue virus infection spreads from an undifferentiated fever and dengue fever (DF) to dengue haemorrhagic fever (DHF) with shock. Factors responsible for bleeding manifestations in dengue are vasculopathy, thrombocytopenia, coagulopathy, and disseminated intravascular coagulation (DIC). Coagulopathy results in derangement of activated partial thromboplastin time (APTT) which is an indicator of impending bleeding risk. Methods: A prospective study was conducted from June to December in 2017 in R L Jalappa Hospital. Patients aged above 18 years with febrile thrombocytopenia who are positive for dengue virus serology (NS1Ag and/ or IgM) were included in the study. Serial daily monitoring of platelet count and analysis of APTT levels were done. APTT was considered abnormal if it was more than 33.8s. Patients were followed up for evidence of leaking and bleeding manifestations. Results: Out of 170 patients 28.1% patients had bleeding manifestations. Bleeding signs were seen on clinical examination in 52.37% of patients. capillary leak was found in the form of Pleural effusion in 35.3%, Ascites in 41.2% and Periorbital edema in 31.2% of patients. Elevated APTT levels were seen in 110(64.7%) patients. Among patients with abnormal APTT platelet transfusion was done in 78.9% of patients, and among those with normal APTT levels platelet transfusion was done in 21.1% of patients. Conclusions: Our study showed significant correlation between bleeding manifestations and prolonged APTT levels as well as thrombocytopenia with abnormal APTT levels. Study concluded that 21.1% of platelet transfusions could have been prevented considering prolonged APTT as a predictor of bleeding manifestation, thus saving the resources and reactions due to platelet concentrate transfusion.